La casualità della vita quotidiana può determinare ciò che deve essere punito? Un programma di ricerca per l’extrema ratio - Marra, Gabriele (Cultura giuridica e diritto vivente, 2018)
Can the casuality of everyday life determine what should be punished? A research program for extrema ratio] The last resort principle (extrema ratio) is deeply rooted in the debate on the limits of criminalization. Nevertheless, overcriminalization is a feature of modern criminal law experience. Many are the reasons of this paradox; among these, the lack of an in-depth analysis of the content of the extrema ratio. The article try to fill this gaps arguing that the real meaning of the last resort principle is the protection of the spontaneous social orders.